2021
DOI: 10.1029/2021gl092549
|View full text |Cite
|
Sign up to set email alerts
|

Detectable Increases in Sequential Flood‐Heatwave Events Across China During 1961–2018

Abstract: Weather and climate extremes are critical drivers for deadly and costly natural disasters (IFRC, 2020; UN-DRR, 2020). Understanding their changes and causes have been staying high on the agenda of climate science and risk management sectors (Chen, Moufouma-Okia, et al., 2018). There is rising awareness that the impact of spatially and/or temporally correlated events tends to be disproportionately larger than that of singular hazards as well as the sum of them (Zscheischler et al., 2018). A new paradigm that mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 81 publications
2
74
0
Order By: Relevance
“…Our present study provides the first examination of the changes in compound heat-precipitation events in South China and quantifies the urbanization effects on these changes by classifying the stations into urban and non-urban ones. Chen et al (2021) has studied another type of compound event, i.e., sequential flood-heatwave events across China, and found that anthropogenic forcings contributed greatly to these compound extremes. Nevertheless, to what degree local urbanization influences the compound events has not been evaluated and needs to be further investigated.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Our present study provides the first examination of the changes in compound heat-precipitation events in South China and quantifies the urbanization effects on these changes by classifying the stations into urban and non-urban ones. Chen et al (2021) has studied another type of compound event, i.e., sequential flood-heatwave events across China, and found that anthropogenic forcings contributed greatly to these compound extremes. Nevertheless, to what degree local urbanization influences the compound events has not been evaluated and needs to be further investigated.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Moreover, floods that follow heat waves have been identified across the central United States , and this compound is manifested by the fact that heat stress may set the stage for extreme precipitation and flooding due to increasing sensible heat flux and moisture convergence under extreme heat stress. Similarly, the floods followed by elevated heat have also been identified across China during 1961-2018, exhibiting an increasing trend (Chen et al, 2021). Western Japan experienced catastrophic floods followed by a record-breaking heatwave during early July 2018 (Wang S. S.-Y.…”
Section: Flooding/precipitation and Heat Wave/ Stressmentioning
confidence: 91%
“…FIGURE 2 | Schematic of compound hydrometeorological extremes: (A) heat-wet (Soneja et al, 2016;Wang S. S.-Y. et al, 2019;Imada et al, 2019;Chen et al, 2021), (B) heat-humid extremes (Fischer and Knutti, 2013;Li et al, 2020;Poppick and McKinnon, 2020;Yuan et al, 2020), (C) cold-wet (Bisci et al, 2012;Hao et al, 2018;Hochman et al, 2019;De Luca et al, 2020) and (D) cold-dry (Dabhi et al, 2018;Wu Y. et al, 2021;Potopová et al, 2021). The Clausius-Clapeyron scaling represents the water holding capacity of the atmosphere corresponding to air temperature changes (Held and Soden, 2006).…”
Section: Typesmentioning
confidence: 99%
See 2 more Smart Citations